Peranan Dark Trait Personality Terhadap Problematic Social Media Use - Disse Rachmadina Habibah (Pusat Riset dan Inovasi Nasional, 2023)
Problematic Social Media Use (PSMU), namely being too busy with social media, having a strong or uncontrollable motivation to use social media, and spending too much time and effort on social media that causes disruption to social life, personal or other people, and health psychological and well-being. PMSB is complex and is formed by many factors, including biological, psychological, social, and cultural. In addition, interrelated factors such as personality, environmental factors, and behavioral systems can develop behavior problems such as PMSB. The purpose of this research is to find out whether there is a role of Dark Trait Personality (DTP) with Problematic Social Media Use (PSMU). The subjects in this study were 202 early adults who used social media. The instruments used were the Short Dark Triad Scale (SD3), Short Sadistic Impulse Scale (SSIS), and Bergen Social Media Addiction Scale (BSMAS). The analysis technique used is process by Hayes. The results of the study have a positive significance (0.00 > 0.05), which means that the higher the Dark Characteristics namely Psychopathy, Makiavelianism, /narcissism, and Sadism that a person has, then a person will tend to increasingly use his social media with bad or negative purposes so that have negative consequences for him. The results also show that there are a number of roles assigned by Dark Trait Personality (DTP) to Problematic Social Media Use (PSMU) of 27.1%, while the rest are influenced by other factors.